Kurva Laktasi Induk Domba Jonggol (Domba Ekor Tipis) Berdasarkan Umur Induk yang Dipelihara dengan Sistem Penggembalaan Grazing System - Jarmuji Jarmuji (Jurnal Sain Peternakan Indonesia, 2014)
ABSTRACTThe objectives of this research were to know the effect of ewe’s age on curve of milk yield reared on grazing. This research was done in The Jonggol Animal Science Teaching, and Research Unit (JASTRU) located in Singasari Village, Jonggol, Bogor district. As many 100 local sheep comprises of pregnant and lactating ewes on average 1-4 years old were used in this research. The sheeps were grazed from 9 a.m. to 4 p.m. and housed on night. The result showed that ewe’s age different effect its of curve milk yield. Lactation peak is expected within 1-2 weeks of lambing, followed by a decreasing phase to the 16 weeks. Decreace of theewes 1 year age showed is not stable if comparation the ewes 3-4 year age.Key words : ewes, curve milk yield,grazing system.